HUBUNGAN ANTARA POLA ASUH PERMISIF ORANGTUA DAN KECERDASAN EMOSIONAL SISWA DENGAN HASIL BELAJAR MATEMATIKA SISWA - Ulfiani Rahman; Mardhiah Mardhiah; Azmidar Azmidar (Auladuna: Jurnal Pendidikan Dasar Islam, 2015)
Abstract: The objective of the research was to find out the relationship between parents permissive conduct and students emotional intelligence towards students mathematics learning achievement. at SMP Negeri 7 Alla Enrekang, South Sulawesi. The findings showed that: (1) there was a relationship between parents permissive conduct and students emotional intelligence towards students mathematics learning achievement; (2) there was a negative relationship between parents permissive conduct and students mathematics learning achievement; (3) there was a positive relationship between students' emotional intelligence and  their 'mathematics learning achievement; and 4) there was a positive relationship between parents permissive conduct and students emotional intelligence.Abstrak: Penelitian ini bertujuan menemukan hubungan antara pola asuh permisif orangtua dan kecerdasan emosional siswa dengan hasil belajar matematika siswa SMP Negeri 7 Alla Kabupaten Enrekang, Sulawesi Selatan. Hasil penelitian menunjukkan: 1) ada hubungan antara pola asuh permisif orangtua dan kecerdasan emosional siswa dengan hasil belajar matematika siswa; 2) ada hubungan negatif antara pola asuh permisif orangtua dengan hasil belajar matematika siswa; 3) ada hubungan positif antara kecerdasan emosional siswa dengan hasil belajar matematika siswa; 4) ada hubungan positif antara pola asuh permisif orangtua dengan kecerdasan emosional siswa.